Collaborative Governance in CSR Implementation: A Case Study of PT Aneka Tambang - Anshar Anshar; Abd. Haris Rahim (Information Technology and Science (ITScience), 2026)
This study examines the implementation of collaborative governance in the Corporate Social Responsibility (CSR) programs of PT Aneka Tambang Tbk in Tambea Village, Pomalaa District, Kolaka Regency, Indonesia. The research focuses on stakeholder collaboration, community participation, facilitating and constraining factors, and the sustainability of CSR initiatives in promoting community empowerment within a mining area. A qualitative descriptive approach was employed. Data were collected through observations, in-depth interviews, and document analysis involving company representatives, village government officials, community leaders, youth and women’s groups, CSR beneficiaries, and local business actors. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that collaborative governance in CSR implementation has involved three key actors: the company, the village government, and the local community. Community participation was relatively strong during the implementation and monitoring phases; however, involvement in planning and evaluation remained limited. The effectiveness of collaboration was supported by the company’s commitment to CSR, active support from the village government, stakeholder communication forums, and relatively harmonious social relations. Nevertheless, several challenges persisted, including limited community capacity, inadequate transparency of program information, unequal distribution of benefits, and dependency on company assistance. Overall, the CSR programs contributed positively to community participation and local economic empowerment. However, strengthening community capacity, improving transparency, and expanding participatory engagement are essential to ensure the long-term sustainability of CSR initiatives in mining communities.